THE ADDED VALUE OF STATE-OWNED HOSPITALSIN CONDUCTING CLINICAL TRIALS - M. Nedelchev1; Y. Nedelcheva (Trakia Journal of Sciences, 2025)
Objective: The object of the article is to review the clinical trials conducted in Bulgarian state-owned hospitals during the COVID-19 pandemic (2019-2022). Material and methods: We have created a unique database of clinical trials from public registers of competent authorities. Our review is based on the content of the protocols of 550 clinical trials conducted in all 62 state-owned hospitals. Results: The number of clinical trials is decreasing, as is the number of trial centres in state-owned hospitals. The clinical trial sector will not go back to pre-pandemic levels, as we predict for the year after the pandemic (2023). In the new reality, reduced budget and declined state funding, the attitudes of state-owned hospitals and patients are shifting towards the benefits of clinical trials. The primary motive for state-owned hospitals to conduct clinical trials is not revenues, but rather access to new drugs and treatment methods. Conclusions: We explain the decline in the number of clinical trials with the national measures addressed to the challenges of the COVID-19 pandemic. The therapeutic area of clinical trials is tailored to the local demographic trend and is not aligned to the most common diseases in Bulgaria. Therefore, Bulgaria is more of a market for the launching tested drugs than a market for testing new drugs.